Role of Electronic Perturbation in Stability and Activity of Pt-Based Alloy Nanocatalysts for Oxygen Reduction - Hwang, Seung Jun; Kim, Soo-Kil; Lee, June-Gunn; Lee, Seung-Cheol; Jang, Jong Hyun; Kim, Pil; Lim, Tae-Hoon; Sung, Yung-Eun; Yoo, Sung Jong (AMER CHEMICAL SOC, 2012)
The design of electrocatalysts for polymer electrolyte membrane fuel cells must satsify two equally important fundamental principles: optimization of electrocatalytic activity and long-term stability in acid media (pH <1) at high potential (0.8 V). We report here a solution-based approach to the preparation of Pt-based alloy with early transition metals and realistic parameters for the stability and activity of Pt3M (M = Y, Zr, Ti, Ni, and Co) nanocatalysts for oxygen reduction reaction (ORR). The enhanced stability and activity of Pt-based alloy nanocatalysts in ORR and the relationship between electronic structure modification and stability were studied by experiment and DFT calculations. Stability correlates with the d-band fillings and the heat of alloy formation of Pt3M alloys, which in turn depends on the degree of the electronic perturbation due to alloying. This concept provides realistic parameters for rational catalyst design in Pt-based alloy systems.
Keywords: DENSITY-FUNCTIONAL THEORY; SURFACE-COMPOSITION; PLATINUM; ELECTROCATALYSIS; CATALYST; DISSOLUTION; TRENDS; METAL; ELECTROREDUCTION; SPECTROSCOPY